The Me and the Us of Emotions: a cluster-randomized controlled trial of the feasibility and efficacy of a compassion-based social–emotional learning program for children - Xavier, Ana; Vagos, Paula; Palmeira, Lara; Menezes, Paulo; Patrão, Bruno; Mendes, Sofia Abreu; Tavares, Marta (Frontiers in Psychology, 2023)
There are well-established benefits of social and emotional learning (SEL) programs for children within educational contexts. Combining social-emotional skills and compassion abilities has been seldomly done, and it may be valuable at individual and societal levels, for resilient, empathetic, and inclusive societies. This study explored the feasibility and efficacy of a program designed to promote socioemotional and compassion skills in children attending the 3rd and 4th grades, by using in-class dynamics complemented with serious games. This program, named "The Me and the Us of Emotions", is part of the Gulbenkian Knowledge Academies 2020 and consists of 10 group sessions embedded in the school curriculum. Using a cluster-randomized controlled trial design, school classes were allocated to intervention (classes, n = 8; children, n = 163) and control groups (classes, n = 6; children, n = 132). During the program, facilitators assessed adherence to the sessions' plan, attendance, dosage (i.e., how many sessions were delivered), and participant responsiveness. Children completed self-report measures of social-emotional skills and emotional climate at pre-, postintervention, 3-month, and 6-month follow-ups. Results indicate that the program is feasible, with high adherence, high attendance rate, and participant responsiveness. Results also indicate empathy, soothing, and drive feelings to change from pre-intervention to all other assessment moments, for the intervention group only. Moreover, cooperation and threat changed over time for participants in both the control and the intervention groups. The current study offers empirical support for the feasibility and utility of a compassion-based social-emotional learning program on promoting children's empathy, and emotions of soothing and vitality in the school context. Thus, these findings contribute to recent research on the potential added value of compassion practices within an SEL program.